Identification of ancient gilding technology and Late Bronze Age metallurgy by EDXRF, Micro-EDXRF, SEM-EDS and metallographic techniques - Figueiredo, Elin (2013)
A combination of analytical techniques capable of elemental and microstructural characterisation was used for the identification of ancient gilding technology and bronze metallurgy. EDXRF, micro-EDXRF, SEM-EDS analysis and metallographic examinations were applied in the study of artefacts dating to the end of the second millennium BC from Crasto de São Romão in Central Portugal. Results report to the finding of an exceptional gilded copper nail among bronze artefacts with 9 wt.% to15 wt.% tin and minute other metallic impurities. Additionally, analysis of a crucible fragment points out for bronze production at the archaeological site. EDXRF and micro-EDXRF analysis made on the copper nail showed that it was gilded only on the front side of the head, and that the gold layer has been lost in the most exposed areas. SEM-EDS analysis showed that the gold layer has 5–8 μm in thickness and is covered with a thick corrosion layer. The gilding technique is discussed based on the gold layer composition and gold/copper substrate interface. So far, this object seems to be the first diffusion gilded artefact identified in the Portuguese territory dated to Late Bronze Age.